INVESTMENT FEASIBILITY ANALYSIS OF PAYBACK PERIOD AND NET PRESENT VALUE METHODS IN SOE BANKING - Yuningsih, Ayu; Aminda, Renea Shinta; Nurhayati, Immas (Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the feasibility of investment to be invested in the banking subsector, especially in State-Owned Commercial Banks (SOEs). The analysis used in this study is descriptive quantitative analysis with Payback Period and Net Present Value methods. Based on the results of the calculation of the payback period, it is possible to know the level of investment eligibility in Bank BRI, Bank Mandiri, Bank BNI, and Bank BTN (BUMN) for the five-year period 2017–2021. The rate of prediction is said to be reasonable or acceptable, that is, in BRI Bank due to the faster rate of return on investment. Based on the results of the calculation of Net Present Value at Bank BRI, Bank Mandiri, Bank BNI, and Bank BTN (BUMN) for the period 2017 to 2021, the level of investment eligibility is accepted or eligible because of a net present Value >0